Care service supply’s impact on household consumption inequality in the context of “one old and one young” families - Dong, Bolin; Liu, Huan (Frontiers in Public Health, 2025)
IntroductionWith aging and family nuclearization, providing care for older adults and children has become a global issue. This study empirically examines the impact of care service supply on household consumption inequality.MethodsData from the China Family Panel Studies are analyzed using the ordinary least squares estimation method.ResultsFirst, childcare and older adult care significantly impact household consumption inequality by 0.23 and 0.35%, respectively. Further, their impacts on household consumption inequalities at different inequality levels show gradually increasing trend. Moreover, significant group heterogeneity is observed in the impact coefficients. Second, under the dual care pressures for childcare and older adult care, the supply of dual-care services significantly affects household consumption inequality by 0.05%.ConclusionCare service supply has an income effect; that is, the supply of family care services affects household consumption inequality by influencing household income inequality. Policy considerations include improving the precision of social welfare and assistance policies, and enhancing the supply mechanism of care services.